RETROCAVAL URETER - Muhammad Akram Malik; Muhammad Sohail (Journal of University Medical & Dental College, 1970)
ABSTRACT Retrocaval ureter or paracaval ureter is a rare congenital abnormality in which ureter passes behind the inferior vena cava from medial to lateral side, causing obstruction which leads to hydronephrosis and lumbar pain. Intravenous urography, retrograde pyelography, CT, and MRI are main diagnostic investigations. Surgical intervention is required in most of cases. We present a case of 24 year old male which presented with right flank pain. Diagnosis was conformed by IVU and retrograde D-J Stenting. Exploration of ureter, its transaction and end to end anastomosis was done anterior to right ureter.